Weed flora of different farm blocks in Block-1 of Muda rice granary in Peninsular Malaysia - Begum, Mahfuza; Juraimi, Abdul Shukor; Man, Azmi; Syed Rastan, Syed Omar; Amartalingam, Rajan (Penerbit Universiti Sains Malaysia, 2008)
A survey on the major weed flora of rice fields in Block-1 of Muda rice granary area, Peninsular Malaysia, indicated there were 28 weed species belonging to 15 families in this area. Of these, 13 species were broad-leaves, six grasses, six sedges, and three aquatics. Sorenson’s Index of Similarity (S) indicated that at least 24.2% of the listed species occurred in five blocks. Oryza sativa complex (padi angin) and Echinochloa crus-galli appeared wide spread species in all blocks, but were most abundant in block AI, BI and DI having a greater proportion of severe infestations (scores of 3 to 5: 31%–50% weed cover). Leptochloa chinensis was the most frequent and abundant species in block AI and EI having the severity score of 3, i.e. 30% and 20% (score of 2) weed coverage in block BI and CI, respectively. Other weed species such as Ischaemum rugosum, Fimbristylis miliacea, Scirpus grossus, Sphenoclea zeylanica and Cyperus difformis were having 20% (score of 2) weed coverage. The hierarchy of weed type based on the percentage of field infested ratio was in the order of: grasses (G) > broad-leaved weeds (BL) > sedges (SG) > aquatics (AQ) in all blocks with a slight difference in block AI, where sedges were dominant instead of broad-leaved weeds, aquatic weeds were totally absent and grasses were predominant as compared to other blocks.